RETRACTED: Analysis of the Effect of Lightning Strikes on Travelling Wave Signal (TWS) in Determining Interference Points on 150 kV Transmission Lines (Glugur-Paya Geli Substation) - Frengki Ditus Laia; Harry Hendra Manalu; Farsya Alfitri Nasution; Rinistin Dachi; Immanuel Roni Gultom; Yoga Tri Nugraha (Journal of Renewable Energy, Electrical, and Computer Engineering, 2023)
This paper has been found to be in violation of the Journal of Renewable Energy, Electrical, and Computer Engineering (JREECE) of the publication principles and has been retracted.Reasons for withdrawal: There has been a conflict of ownership in this manuscript, so carefully concerns and considered review of the article published in Journal of Renewable Energy, Electrical, and Computer Engineering (JREECE) to article entitled Analysis of the Effect of Lightning Strikes on Travelling Wave Signal (TWS) in Determining Interference Points on 150 kV Transmission Lines (Glugur-Paya Geli Substation) Vol 3, No 1, pp. 1-5, March 2023, DOI: https://doi.org/10.29103/jreece.v3i1.9395The document and its content has been removed from Journal of Renewable Energy, Electrical, and Computer Engineering (JREECE), and reasonable effort should be made to remove all references to this article.